Effect of High-Calorie Diet and Moderate-Intensity Physical Exercise on Gastric Histopathological Features of Mice - Zamzam, Ramadhani Rizki; Irwadi, Irfiansyah; Rahniayu, Alphania (Current Internal Medicine Research and Practice Surabaya Journal, 2024)
Introduction: Habit of consuming excess calories and sedentary lifestyle can cause oxidative stress which is known to be involved in the pathophysiological process of various diseases including diseases of the gastrointestinal mucosa. Increased Reactive Oxygen Species (ROS) due to a high-calorie diet can damage lipids, proteins, and DNA oxidation of the mucosa and lead to inflammation, apoptosis, damage of mucosal and its barrier. Moderate-intensity physical exercise is known to have health benefits, improve quality of life, reduce the risk of death, and prevent the occurrence of diseases related to oxidative stress. The aim of this study was to analyze the effect of high-calorie diet and moderate-intensity physical exercise on gastric histopathological features of mice.Methods: This research was a true experimental study with posttest only control group design. Female Balb/C strain were randomly assigned into three groups, the control group/K1 (n=12), high-calorie diet group/K2 (n=12), and high-calorie diet and moderate-intensity physical exercise group/K3 (n=9). High-calorie diet in the form of dextrose (D40) was given ad libitum using sonde in a dose of 3-5% of calories or 0.0325 mL/gBW. The moderate-intensity physical exercise was carried out by swimming three times a week for 15 minutes using 6% gBW loading. After 4 weeks of treatment, the mice were sacrificed and their stomach were sampled and prepared for microscopic analysis.Results: The histopathological examination of the gastric mucosa showed the average number of inflammatory cells was 11.60 for K1, 11.25 for K2, and 14.5222 for K3. The Shapiro-Wilk test revealed that the data on inflammatory cells infiltrations were not normally distributed (p<0.05), so a non-parametric difference test was conducted using the Kruskal-Wallis test. Based on the Kruskal-Wallis test results, it was obtained that p>0.05, which means no significant difference was found between the three study groups.Conclusion: There was no effect of a high-calorie diet and moderate-intensity physical exercise on the gastric histopathological features of mice (Mus musculus) in this study